Energy audits in a private firm environment: Energy efficiency consultants' cost calculation for innovative technologies in the housing sector - Daniel Feser; Kilian Bizer; Annette Rudolph-Cleff; Joachim Schulze (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2016)
During recent international climate negotiations like in Paris 2015, the European Union agreed to reduce the emissions of greenhouse gases. Policy-makers target the residential sector as a major user of fossil energy because potential to improve the energy efficiency in existing houses is observable. Energy audits have been implemented to offer information to homeowners within the aim of reducing the uncertainty concerning energetic refurbishment. Nevertheless, the impact of energy efficiency consultants (EECs) on retrofit measures is described as low in the literature. We conducted an online survey on German EECs, emphasizing their personal attitudes and contextual conditions, analyzing the implementation of an exploratory energy audit and providing recommendations for improving energy audits. The EECs answered the questions regarding the personal factors in a highly confident way. We explain this using the market framework in Germany, which requires a high-level performance due to the competition on the EEC market. The contextual conditions are evaluated critically, with about 49% expressing concerns about acquiring and managing financial resources for energy audits. The case study showed that EECs recommend innovative technologies to a limited degree, while the upfront costs are estimated very low. Finally, in the survey, the respondents prioritized an information policy improvement.
Keywords: 330; energy audits; change agents; energy policy; diffusion of innovation